Isolation and presumptive identification of cellulolytic bacteria from soil sample and characterization of crude cellulase - Khan, Sazzad (BRAC University, 2017)
This Thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2016.